Leadership styles and qualities of the head as the main components of effective management of the social service under martial law conditions - Puzyrova, Olha (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*380.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912234);" role="presentation">The article is devoted to the review and analysis of the types of management styles and qualities of the head of <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*392.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955557);" role="presentation">the social service. The importance of studying changes in the system of relations «<span dir="ltr" style="left: calc(var(–scale-factor)*405.31px); top: calc(var(–scale-factor)*392.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916347);" role="presentation">The head – <span dir="ltr" style="left: calc(var(–scale-factor)*456.91px); top: calc(var(–scale-factor)*392.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91766);" role="presentation">The subordinate» <span dir="ltr" style="left: calc(var(–scale-factor)*531.94px); top: calc(var(–scale-factor)*392.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922683);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*403.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989554);" role="presentation">justified in view of certain problems and difficulties in the work of social services under martial law conditions in <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*415.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930259);" role="presentation">Ukraine. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*426.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906676);" role="presentation">The article uses met<span dir="ltr" style="left: calc(var(–scale-factor)*173.54px); top: calc(var(–scale-factor)*426.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93778);" role="presentation">hods of analysis and generalization to clarify the definition of the term “leadership styles” <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*438.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924836);" role="presentation">as well as groups important personal and professional qualities of the head. The empirical basis of the article is results <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*449.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954989);" role="presentation">of in-depth interviews conducted with the heads of social services, public organizations and charitable foundations, <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*461.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955623);" role="presentation">implemented within the scientific theme «<span dir="ltr" style="left: calc(var(–scale-factor)*231.05px); top: calc(var(–scale-factor)*461.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945072);" role="presentation">Actual directions of management of social services» <span dir="ltr" style="left: calc(var(–scale-factor)*451.39px); top: calc(var(–scale-factor)*461.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959397);" role="presentation">of the Department of <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*472.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956792);" role="presentation">Sociology of Management and Social Work of V. N. Karazin Kharkiv <span dir="ltr" style="left: calc(var(–scale-factor)*344.95px); top: calc(var(–scale-factor)*472.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953389);" role="presentation">National University. According to the results of <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*484.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961717);" role="presentation">the research, several groups of qualities of the head (professional, leadership, personal and communicative) were <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*495.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925226);" role="presentation">formed by author, which are relevant for the realization of managerial influence under condi<span dir="ltr" style="left: calc(var(–scale-factor)*427.99px); top: calc(var(–scale-factor)*495.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916235);" role="presentation">tions of stable situation and <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*507.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934829);" role="presentation">during the period of martial law in the country. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*518.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.980344);" role="presentation">Based on the analysis of the advantages and disadvantages of different management styles, the author <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*530.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927675);" role="presentation">concluded that it is necessary to situationally apply a set of techniques and methods of management which inherent in <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*541.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915404);" role="presentation">democratic and directive styles in war conditions. The results of empirical research have proved that in the conditions of <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*553.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928879);" role="presentation">threats and risks, limited recourses, high workload on employees, the role of the complex of leadership qualities of the <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*564.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911983);" role="presentation">head is significantly increased. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*576.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924574);" role="presentation">A head-leader must be able to not only to organize work activities and regulate formal labor relations, but also <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*587.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904856);" role="presentation">to inspire employees, encourage them to achieve goals and maintain positive social and psychological atmosphere in the <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*599.23px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927351);" role="presentation">organization. Personal characteristics of the manager, such as empathy, humanity and attention to subordinates, have <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*610.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.988342);" role="presentation">become important for the moral and psychological support of service personnel in wartime, when, in addition to <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*622.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915308);" role="presentation">difficulties arising in the labor process, there is a real threat to safety and life.